PENGARUH TEKNIK TOKEN EKONOMI TERHADAP KEMANDIRIAN ANAK USIA 5-6 TAHUN DI KELOMPOK BERMAIN (KB) HANG KESTURI KECAMATAN PEKANBARU KOTA - Suryani, Suryani; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study Aims To Know How Much Influence of Mechanical Token Economy Against Children Aged 5-6 Years Independence In Playgroup (KB) Hang Kesturi District of Pekanbaru City. This research Consists Of Two Variables: Mechanical Toekn Economic and Independence Children. Proposed hypothesis in this study are the following: There Effect of Mechanical Token Economy Against Children Aged 5-6 Years Independence In Group Play Hang Kesturi District of Pekanbaru City. The study involved 16 subjects, namely 5-6 years old. Methods of data collection in this study using experimental. Data analysis techniques used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos.The results showed no significant positive relationship between the independence of Mechanical Token Economy Against Children Aged 5-6 Years In Group Play Hang Kesturi District of Pekanbaru City. Based on the results of the test results of the child's independence difference after using the Technique Token Economy Mechanical influences are 45.13% Token Economy Against Independence.Keywords: Mechanical Token Economy, Independence